Collaboration imprint for entrepreneurs in innovative projects - FAN, Terence P. C. (Institutional Knowledge at Singapore Management University, 2016)
This paper explores how entrepreneurs learn to improve performance in a series of innovative projects that involve more complexity than those repetitive tasks. We propose that collaborating with a specific set of partners can generate a characteristic creative mood and routine, leaving a distinctive impact on the performance of future project outcomes. Over multiple innovative endeavors, collaborating with different sets of partners helps a focal entrepreneur explore and experiment with different facets of his or her creativity, achieving a variety of outcomes. We propose to test the lasting impact of collaboration using the commercial performance of early software applications (‘apps’) developed for use in the Facebook social network medium.